UMPSA strengthens research ties with Indonesia’s National Research and Innovation Agency (BRIN) - Mirta, Widia (UMPSA, 2025)
JAKARTA, 15 August 2025 - A delegation from Faculty of Industrial Sciences and Technology (FIST), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), represented by members of the Occupational Safety and Engineering Research Group (OSERa), OSHE Cluster, visited two key research centres under Indonesia’s National Research and Innovation Agency (BRIN).